An observational test for star formation prescriptions in cosmological hydrodynamical simulations. Issue 1 (5th April 2019) - Buck, Tobias; Dutton, Aaron A; Macciò, Andrea V
Abstract: State-of-the-art cosmological hydrodynamical simulations of galaxy formation have reached the point at which their outcomes result in galaxies with ever more realism. Still, the employed sub-grid models include several free parameters such as the density threshold, n, to localize the star-forming gas. In this work, we investigate the possibilities to utilize the observed clustered nature of star formation (SF) in order to refine SF prescriptions and constrain the density threshold parameter. To this end, we measure the clustering strength, correlation length, and power-law index of the two-point correlation function of young (τ < 50 Myr) stellar particles and compare our results to observations from the HST Legacy Extragalactic UV Survey (LEGUS). Our simulations reveal a clear trend of larger clustering signal and power-law index and lower correlation length as the SF threshold increases with only mild dependence on galaxy properties such as stellar mass or specific star formation rate. In conclusion, we find that the observed clustering of SF is inconsistent with a low threshold for SF ( n < 1 cm −3 ) and strongly favours a high value for the density threshold of SF ( n > 10 cm −3 ), as, for example employed in the NIHAO project.